Carotid artery atherosclerosis is associated with mortality in HIV-positive women and men. (23rd October 2018) - Hanna, David B.; Moon, Jee-Young; Haberlen, Sabina A.; French, Audrey L.; Palella, Frank J.; Gange, Stephen J.; Witt, Mallory D.; Kassaye, Seble; Lazar, Jason M.; Tien, Phyllis C.; Feinstein, Matthew J.; Kingsley, Lawrence A.; et al.
Abstract : Objective: Among people with HIV, there are few long-term studies of noninvasive ultrasound-based measurements of the carotid artery predicting major health events. We hypothesized that such measurements are associated with 10-year mortality in the Women's Interagency HIV Study (WIHS) and Multicenter AIDS Cohort Study (MACS), and that associations differ by HIV serostatus. Design: Nested cohort study. Methods: Participants without coronary heart disease underwent B-mode carotid artery ultrasound, with measurement of common carotid artery intima–media thickness (IMT); carotid artery plaque (focal IMT > 1.5 mm) at six locations; and Young's modulus of elasticity, a measure of arterial stiffness. We examined all-cause mortality using Cox models, controlling for demographic, behavioral, cardiometabolic, and HIV-related factors. Results: Among 1722 women (median age 40 years, 90% nonwhite, 71% HIV-positive) and 1304 men (median age 50, 39% nonwhite, 62% HIV-positive), 11% died during follow-up. Mortality was higher among HIV-positive women [19.9 deaths/1000 person-years, 95% confidence interval (CI) 14.7–28.8] than HIV-positive men (15.1/1000, 95% CI 8.3–26.8). In adjusted analyses, plaque was associated with mortality (hazard ratio 1.44, 95% CI 1.10–1.88) regardless of HIV serostatus, and varied by sex (among women, hazard ratio 1.06, 95% CI 0.74–1.52; among men; hazard ratio 2.19, 95% CI 1.41–3.43). The association of plaque with mortality was more pronounced among HIV-negative (hazard ratio 3.87, 95% 1.95–7.66) than HIV-positive participants (hazard ratio 1.35, 95% CI 1.00–1.84). Arterial stiffness was also associated with mortality (hazard ratio 1.43 for highest versus lowest quartile, 95% CI 1.02–2.01). Greater common carotid artery-IMT was not associated with mortality. Conclusion: Carotid artery plaque was predictive of mortality, with differences observed by sex and HIV serostatus. Abstract : Supplemental Digital Content is available in the text